Prime ministerial careers in the European Union: does gender make a difference?. Issue 2 (3rd April 2017) - Müller-Rommel, Ferdinand; Vercesi, Michelangelo
ABSTRACT: This article presents empirical findings on two questions: what are the 'political stepping stones' on the way to the prime ministerial post? Are there any differences between female and male prime ministers on their way to the chief executive? These questions are primarily linked to the literature on women's recruitment in top political offices. The data for this analysis stem from unique biographical records of 76 prime ministers in those 10 member states of the European Union where women have been in prime ministerial positions from 1979 to 2015. Consistent with theoretical expectations, the empirical findings show that there is indeed a gender difference in the pathways to the prime ministerial post. Female prime ministers are predominantly recruited in centre-right parties. They have more political experience in parliament and cabinet than their male counterparts, but a shorter duration in office once becoming prime minister.